PEMBERDAYAAN KETERAMPILAN RETORIKA DAKWAH SANTRI PONDOK PESANTREN MIFTAHUL ULUM PANDEAN WONOREJO BANYUPUTIH SITUBONDO - Nur Ainiyah (LP2M Universitas Ibrahimy, 2019)
This assistance is aimed to train students in improving speaking skills in order to make easy in conveying messages and ideas to others. It is Located in Miftahul Ulum Islamic Boarding School. It has two research problems, they are, (1) How is the speaking skill empowerment through discourse techniques to the students in building public speaking communication? (2) How are the obstacles faced by students in Miftahul Ulum Islamic Boarding School?. The assistant explores interview data and documentation data by the data analysis technique. The results show that (1) The activities of muhadharah discourse training in Miftahul Ulum Islamic Boarding School is carried out once a week on Saturday evening. (2) With great motivation, the students will carry out activities with focus on the objectives of the learning process. (3) Muhadharah is carried out by all caretakers and all students in Miftahul Ulum Islamic Boarding School.